2020
DOI: 10.1371/journal.pone.0242609
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of grassland NPP in Gansu province, China from 1982 to 2011 and its impact factors

Abstract: The modified Carnegie–Ames–Stanford Approach (CASA) model based on the comprehensive and sequential classification system of grasslands (CSCS, a unique vegetation classification system) was used to determine grassland net primary production (NPP) in Gansu province from 1982 to 2011 and its spatio-temporal variability. The relationship between NPP and climate drivers was analyzed. The results showed that annual NPP of grasslands in Gansu province averaged 139.30 gC m-2 yr -1 during the study period. NPP decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Grassland annual NPP varied significantly across the four grassland types, with a higher annual average NPP in meadow steppe and typical steppe, and a lower annual average NPP in steppe desert and desert steppe (Figure 1a ). Similar results were also reported for the spatial distribution of annual NPP in grasslands in the Gansu Province (Zhang, Liu, et al, 2020 ), where NPP in the southeast (Qilian Mountain, Longnan Mountain, and Gannan Plateau) which is mostly occupied by meadow and typical steppe was highest and NPP in the northwest (Hexi Corridor and North Mountain) which is occupied by steppe desert and desert steppe was lowest (Zhang, Liu, et al, 2020 ). Similarly, investigating the changes of NPP across different biomes for the period 2000–2010, Liu et al ( 2015 ) also reported that NPP in steppe grasslands was higher than that in desert grasslands, which is consistent with our findings where we found NPP was highest in meadow steppe and lowest in desert steppe.…”
Section: Discussionsupporting
confidence: 89%
“…Grassland annual NPP varied significantly across the four grassland types, with a higher annual average NPP in meadow steppe and typical steppe, and a lower annual average NPP in steppe desert and desert steppe (Figure 1a ). Similar results were also reported for the spatial distribution of annual NPP in grasslands in the Gansu Province (Zhang, Liu, et al, 2020 ), where NPP in the southeast (Qilian Mountain, Longnan Mountain, and Gannan Plateau) which is mostly occupied by meadow and typical steppe was highest and NPP in the northwest (Hexi Corridor and North Mountain) which is occupied by steppe desert and desert steppe was lowest (Zhang, Liu, et al, 2020 ). Similarly, investigating the changes of NPP across different biomes for the period 2000–2010, Liu et al ( 2015 ) also reported that NPP in steppe grasslands was higher than that in desert grasslands, which is consistent with our findings where we found NPP was highest in meadow steppe and lowest in desert steppe.…”
Section: Discussionsupporting
confidence: 89%
“…However, the high temperature during growing seasons corresponded to high evapotranspiration, decreasing the amount of water available for grassland growth. Similar relationships between climate patterns and the FSn and grassland NPP were found in other regions in Northwest China [57,58]. For artificial grasslands, scarce precipitation would cause a shortage of irrigation water, resulting in reduced yield.…”
Section: Forage Supply-demand Relationshipssupporting
confidence: 69%
“…NPP was calculated based on the CASA model, although its prediction accuracy is not perfect due to the differences in spatial resolution and the actual and simulated values of variable factors [ 22 ]. Nevertheless, it is widely recognized and applied in numerous macroecological studies [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%